Association between blood pressure control status, visit-to-visit blood pressure variability, and cognitive function in elderly Chinese: A nationwide study - Xu, Luxinyi; Yang, Ying; Cui, Dan (Frontiers in Public Health, 2022)
Background: Cognitive function is a concern among the elderly, which is related to the quality of life, life expectancy, and economic burdens. The relationship between blood pressure (BP) control status, visit-to-visit BP variability, and cognitive function remains controversial. Methods: We aimed to explore the association between BP control status at baseline, visit-to-visit BP variability, and cognitive function. This study included 3511 elderlies in the China Health and Retirement Longitudinal Study, covering four waves for 7-year follow-up (baseline 2011, 2013, 2015, and 2018). BP was measured in Wave 2011, 2013, and 2015. Cognitive function was measured by Mini-Mental State Exam in Wave 2018. Participants were divided into two groups: mid-old group for reflecting midlife BP and cognition (45-59 years at baseline but aged 60 or over in Wave 2018), and old-old group for reflecting late-life BP and cognition (aged 60 or over at baseline). We use univariate analysis and general linear model to analyze. Results: Late-life BP showed stronger associations with cognitive function than midlife BP. As to late-life BP control status, controlled hypertension group get higher cognitive score than uncontrolled hypertension group in language, and untreated hypertension group in orientation, language, and total. Regarding visit-to-visit BP variability, midlife visit-to-visit systolic blood pressure (SBP) variability was associated with language, while late-life visit-to-visit SBP variability was associated with orientation, recall, language, and total; Midlife diastolic blood pressure (DBP) variability and pulse pressure (PP) variability showed a significant relationship with language and calculation, respectively. No significant correlation was found between midlife BP control status, late-life visit-to-visit DBP variability, late-life visit-to-visit PP variability, and cognitive score. There was no significant correlation between BP and memory. Conclusions: BP control status and visit-to-visit BP variability were significantly related to cognitive function among the Chinese elderly. Receiving effective late-life antihypertensive treatment and keeping SBP stable might contribute to prevent the development of cognitive impairment and dementia, especially for orientation and language function.